Partial purification and comparison of precipitation techniques of pyruvate decarboxylase enzyme - Julaluk Tangtua (2018)
© 2017, Chiang Mai University. All rights reserved. The intracellular pyruvate decarboxylase enzyme (PDC, EC 4.1.1.1) extract from Candida tropicalis TISTR 5350 was compared by two different purification methods using ammonium sulphate and acetone precipitation. The total volumetric PDC activity and percentage recovery (yield) of precipitated PDC based on 50% (v/v) cold acetone were significantly higher (1.13 ± 0.02 U/ml and 98.27 ± 2.98 %, respectively) than any other concentration levels of acetone used. Furthermore, all concentration levels of cold acetone also yielded a much higher specific PDC activity than the precipitate obtained using the 40 to 60% (w/v) ammonium sulphate saturation (0.75 ± 0.08 U/mg protein). The precipitated enzyme in buffer solutions from the 50% (v/v) acetone was subsequently freeze dried. Freeze drying of the precipitated PDC by cold acetone resulted in the specific PDC activity of 1.57 ± 0.02 U/mg protein and differed statistically (p ≤ 0.05) from the crude enzyme extract (control).